The Influence of DMBA (7,12-dimethylbenz-[a]anthracene) Regimen In The Development of Mammae CarcinogÃÂ©nesis on Sprague Dawley Female Rat - Wibowo, Agung Eru; Sriningsih, .; Wuyung, Puspita Eka; Ranasasmita, Raafqi (Indonesian Journal of Cancer Chemoprevention, 2010)
There are many methods for developmentÃÂ  of mammae cancer animal model, one of which is chemical induction using carcinogenicÃÂ  agent, DMBA. This research aimed to explore the influence of dose and time regimens of DMBA on development of mammae carcinogenesis on Sprague dawley female rats. The first study was 50 rats treated with 20 mg/kg bw of DMBA orally for eleven times at twice a week. Morphological evaluations were conducted with mammae palpation for 15 weeks and then all ofÃÂ  rats were sacrificed for collecting mammae organs for histological analysis using hematoxylin-eosin staining. The results showed that the first and the latest nodules appeared at the fourth-week and the fourteenth-week after ending DMBA induction, respectively, in which theÃÂ  most often nodule appearances were at the seventh-week. The number of nodule incidence and multiplicity were by 74% and 2 noduls/rat, respectively. Histological analysis of mammae glands determined that they fell under in Ductal Carcinoma Invasive (DCIV) category. The second study was 25 rats gavaged orally with DMBA at dose 20 mg/kg bw for five times every three days. After palpating for 15 weeks, the results showed that no nodule was observed but the histological analysis demonstrated developing of mammae gland carcinogenesis reaching about 60%ÃÂ  Ductal Carcinoma Insitu (DCIS) and 40% Ductal Carcinoma Invasive (DCIV) stages. Based on the results of this study can be concluded that the dose and frequency of DMBA will affect the successful development of mammary gland carcinogenesis. In DMBA induction with low frequency, no data showed the incidence and multiplicity of tumor, but histopathologic levelÃÂ  carcinogenesis can be distinguished. In DMBA induction with high frequency, incidence and multiplicity of tumor data can be obtained but can not be distinguished histopathologically.